Clinicians' experiences of becoming a clinical manager: a qualitative study - Spehar Ivan; Frich Jan C; Kjekshus Lars Erik (BMC, 2012)
Abstract Background There has been an increased interest in recruiting health professionals with a clinical background to management positions in health care. We know little about the factors that influence individuals' decisions to engage in management. The aim of this study is to explore clinicians' journeys towards management positions in hospitals, in order to identify potential drivers and barriers to management recruitment and development. Methods We did a qualitative study which included in-depth interviews with 30 clinicians in middle and first-line management positions in Norwegian hospitals. In addition, participant observation was conducted with 20 of the participants. The informants were recruited from medical and surgical departments, and most had professional backgrounds as medical doctors or nurses. Interviews were analyzed by systemic text condensation. Results We found that there were three phases in clinicians' journey into management; the development of leadership awareness, taking on the manager role and the experience of entering management. Participants' experiences suggest that there are different journeys into management, in which both external and internal pressure emerged as a recurrent theme. They had not anticipated a career in clinical management, and experienced that they had been persuaded to take the position. Being thrown into the position, without being sufficiently prepared for the task, was a common experience among participants. Being left to themselves, they had to learn management "on the fly". Some were frustrated in their role due to increasing administrative workloads, without being able to delegate work effectively. Conclusions Path dependency and social pressure seems to influence clinicians' decisions to enter into management positions. Hospital organizations should formalize pathways into management, in order to identify, attract, and retain the most qualified talents. Top managers should make sure that necessary support functions are available locally, especially for early stage clinician managers.